Simulating Scaling Effects in Fully Vertical GaN FinFETs - Simko, Alexander; Garigapati, Navya Sri; Logotheti, Adamantia ; 0000-0003-1473-2141; Darakchieva, Vanya; Lind, Erik ; 0000-0001-5432-3479 (Physica Status Solidi (A) Applications and Materials Science, 2025)
Herein, it is shown that a fully vertical GaN FinFET can reach close to ideal Baliga's figure of merit (BFOM) for thicker drift layers. Devices with drift layers between 1 and 8 (Formula presented.) are simulated using TCAD, and the device geometry is varied to find optimal device performance. For 8 (Formula presented.) drift layers, device operation at the BFOM limit is found with (Formula presented.) and (Formula presented.). An optimal switching FOM at (Formula presented.) is found.
Publisher Copyright: © 2025 The Author(s). physica status solidi (a) applications and materials science published by Wiley-VCH GmbH.
Keywords: finFETs; GaN; power devices; TCAD